Peramalan Nilai Penjualan Gas Elpiji 3 Kg di Sumatera Utara dengan bantuan Analisis Metode Jaringan Saraf Tiruan - Maulidya Rahma Siregar; Adinda Putri Azhari; Dedy Hartama; Agus Perdana Windarto (Bulletin of Artificial Intelligence, 2022)
This research is related to forecasting the sales value of 3 Kg LPG in North Sumatra. The level of sales is influenced by customer satisfaction, service and customer needs. The purpose of this study is to determine the level of sales of 3 Kg LPG in North Sumatra and can overcome problems and overcome the amount of LPG demand in North Sumatra. So this research is needed using an artificial neural network method with a backpropagation algorithm to find the best sales results. The data used is divided into 2 parts, namely training and test data. The best network is taken from the Mean Square error (MSE) value and the smallest test. The experiments carried out in this study used a data rotation pattern, with 6 training and testing models. The experimental results of the 3-10-1 model are tests with the highest accuracy value, which is 100% and the MSE test is 0.00100005